Down syndrome is associated with altered frequency and functioning of tracheal multiciliated cells, and response to influenza virus infection - Samantha N. Thomas; Brian F. Niemeyer; Rocio J. Jimenez-Valdes; Alexander J. Kaiser; Joaquin M. Espinosa; Kelly D. Sullivan; Andrew Goodspeed; James C. Costello; Jonathan K. Alder; Rodrigo Cañas-Arranz; Adolfo García-Sastre; Kambez H. Benam (iScience, 2023)
Summary: Individuals with Down syndrome (DS) clinically manifest severe respiratory illnesses; however, there is a paucity of data on how DS influences homeostatic physiology of lung airway, and its reactive responses to pulmonary pathogens. We generated well-differentiated ciliated airway epithelia using tracheas from wild-type and Dp(16)1/Yey mice in vitro, and discovered that Dp(16)1/Yey epithelia have significantly lower abundance of ciliated cells, an altered ciliary beating profile, and reduced mucociliary transport. Interestingly, both sets of differentiated epithelia released similar quantities of viral particles after infection with influenza A virus (IAV). However, RNA-sequencing and proteomic analyses revealed an immune hyperreactive phenotype particularly for monocyte-recruiting chemokines in Dp(16)1/Yey epithelia. Importantly, when we challenged mice in vivo with IAV, we observed immune hyper-responsiveness in Dp(16)1/Yey mice, evidenced by higher quantities of lung airway infiltrated monocytes, and elevated levels of pro-inflammatory cytokines in bronchoalveolar lavage fluid. Our findings illuminate mechanisms underlying DS-mediated pathophysiological changes in airway epithelium.